2018
DOI: 10.13005/bpj/1362
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Sinusitis of out Patients ENT Clinic in Sanglah Hospital, Period January to December 2014

Abstract: Sinusitis is a very common disease in Indonesia. Indonesian Health Department in 2003 mentioned that nasal and sinus disease is in 25th of 50 major diseases or about 102,817 outpatients in hospitals. Data from the Division of Rinology of ENT Department of RSCM from January to August 2005 as many as 435 patients or about 69% (300 patients) are sinusitis. Knowing the characteristics of sinusitis patients is very helpful for health professionals in making diagnosis and treatment plan for sinusitis patient. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only.…”
Section: Resultsmentioning
confidence: 99%
“…In adulthood, numerous lifestyle changes, dietary patterns, and infections are prevalent. The adult age group is also more likely to engage in outdoor activities, leading to increased exposure to pollutants and irritants more frequently [15]. Adults face a higher risk of developing rhinosinusitis due to the nasal passages tending to dry with age, weakening of cartilage strength resulting in alterations in blood flow, and a decline in cough and vomiting reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…Dikatakan akut jika infeksi berumur kurang dari 12 minggu, dan kronis jika infeksi berumur lebih dari minggu. 9 Penggunaan proyeksi yang tepat pada saat pemeriksaan sinus paranasal sangat penting untuk menegakkan diagnosa. Menurut penulis penggunaan proyeksi yang berbeda memberikan peluang gambaran yang relatif berbeda, karena setiap proyeksi memiliki fungsi untuk memperlihatkan bagian-bagian tertentu.…”
Section: Pendahuluanunclassified